IMPLEMENTASI APLIKASI WEBSITE E-COMMERCE SEBAGAI UPAYA PENINGKATAN PROMOSI PEMASARAN USAHA KECIL DAN MENENGAH - Muttaqin, Rodhotul (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
Small Business is defined as an economic activity carried out by an individual or a household or an agency aiming to produce goods or services for commercial commission and has a sales turnover of 1 (one) billion rupiah or less. While Medium Business is defined as eco- nomic  activity  conducted  by  individual  or  household  as  well  as  an  agency  aims  to  produce goods or services for commercial commodity and have sales turnover more than 1 (one) billion. One  of  the  SMEs  that  developed  in  Dukuh  Delik  Wringin  Jajar  Village  Mranggen  Dis- trict Demak District is the business of making furniture from aluminum material. This busi- ness has been going on for almost 8 years and able to absorb 5 to 10 workers in the surround- ing  environment.  Fluctuations  in  the  amount  of  labor  depend  heavily  on  orders  demanded by  customers.  Products  produced  by  SMEs  include:  Doors,  Frames,  Window  Leaves,  Kitch- en  Set,  Kitchen  Cabinets,  Storefronts,  Corner  Display  Cabinets,  Rolling  Door  and  others. The   purpose   of   community   service   is   to   help   the   SME   businessman   making   furniture from  aluminum  material  in  Dukuh  Delik  Wringin  Jajar  Village  Mr.anggen  District  De- mak District, especially in the field of marketing. The type of marketing chosen by the dev- otees  team  is  by  creating  an  online  store  based  on  Opensource  CMS  that  is  Prestashop. The outcome of this program is expected the SMEs business of making furniture from aluminum material has the ability in marketing their products through online store application system that has been made. In addition is expected also with the training and assistance provided by these business actors are able to manage online stores independently. So that will affect the amount of production and orders that will be able to improve the living standards of business actors